Comparison of Outcomes Following Infrapopliteal Plain Balloon Angioplasty in the BASIL Trial (1999-2004) and in a Contemporary Series (2009-2013). (February 2020) - Popplewell, Matthew A.; Davies, Huw O.B.; Renton, Mary; Bate, Gareth; Patel, Smitaa; Deeks, Jonathan J.; Bradbury, Andrew W.
Objectives: To compare outcomes in patients randomized to infrapopliteal (IP) plain balloon angioplasty (PBA) for chronic limb-threatening ischemia within the Bypass versus Angioplasty in Severe Ischemia of the Leg (BASIL)-1 trial between 1999 and 2004 with outcomes in consecutive patients undergoing IP PBA at an academic vascular unit a decade later (2009-2013, Contemporary series [CS]). Methods: Individual patient data were obtained from prospective BASIL-1 (48 patients) and CS databases (73 patients). All had a minimum of 3-years of follow-up. Outcomes studied were amputation-free survival (AFS), overall survival (OS), major (above ankle) limb amputation, arterial reintervention, immediate technical success, and length of hospital stay for the index procedure and during the following 12-month period. Statistical analysis was performed using SAS version 9.4. Results: The BASIL and CS cohorts were well matched for gender, age, diabetes, previous stroke, myocardial infarction and arterial intervention, and presence of tissue loss. More patients in BASIL-1 underwent concomitant treatment of the superficial femoral (60% vs 37%, P = .01) and above knee popliteal (60% vs 34%, P = .005) arteries. Immediate technical success increased from 73% in BASIL-1 to 90% in the CS ( P = .01). Between the two cohorts, there were no differences in AFS (hazard ratio [HR] = 1.00, 95% confidence interval [CI]: 0.65-1.54, P = 1.0), OS (HR = 1.04, 95% CI: 0.66-1.62, P = .9), major amputation (HR = 0.86, 95% CI: 0.37-1.97, P = .7), or reintervention (HR = 0.61, 95% CI: 0.29-1.27, P = .2). Contemporary series patients spent significantly fewer days in hospital following the index procedure ( P = .02) and also over the following 12 months ( P = .002). Conclusions: Despite improvements in the immediate technical angiographic success of IP PBA between BASIL and the CS, there were no significant improvements in survival outcomes. Results from BASIL-2 and BEST-CLI are required in order to properly define the clinical and cost-effectiveness of endovascular treatment in such patients.